Emotional intelligence and academic achievement of Philippine Science High School students - De Guzman, Abigail C. (2006)
The Mayer-Salovey-Caruso Emotional Intelligence Test:Youth Version (MSCEIT:YV) was administered to 90 second to fourth year students of the Philippine Science High School (PSHS), Main Campus at Diliman. The EIQs and EI branch scores of 45 students with good academic standing and 45 students with warning or probation were compared to determine if emotional intelligence could explain why some cognitively gifted students have poor academic achievement. The test yields an overall intelligence quotient and four emotional branch scores namely, identifying emotions, using emotions, understanding emotions, and managing emotions. Factoring in independent variables like entrance exam scores, gender, and residence in the multiple regression equation showed 39.90 percent of the change in the year-level weighted average may be explained by the change in the four EI branch scores, entrance test scores, gender and residence.
"October 2006."
Thesis (M. A. Education : Special Education)--University of the Philippines, Diliman.
Keywords: Emotional intelligence -- Philippines -- Quezon City; Academic achievement -- Philippines -- Quezon City